Patterns and influencing factors of smokeless tobacco use among pregnant and lactating mothers in urban slums of bhubaneswar, Odisha - Anna Salomi Kerketta; Arpita Panda; Jayashree Parida; Binapani Nath; Suchismita Swain; Arpita Kar Sharma; Prashant Kumar Singh; Shalini Singh; Sanghamita Pati; Subhendu Kumar Acharya (Scientific Reports)
Abstract Smokeless tobacco (SLT) consumption has several adverse impacts on pregnancy and child health outcomes, particularly among women in low-income settings. SLT use during pregnancy heightens the risks, like preterm births, stillbirth, babies with low birth weight, and small for gestational age. The present qualitative study explored the patterns and contributing factors associated with SLT use behavior among pregnant and lactating mothers in slum settings. We conducted a qualitative study using in-depth interviews among pregnant and lactating women aged 18–49 years in the slums of Bhubaneswar. All participants were current users of smokeless tobacco (SLT) with a history of more than one year of consumption. The interviews were analyzed using a thematic analysis approach. Participants primarily consumed SLT products such as Paan, Khaini, Areca Nut, Gundi, Dukta, Gudakhu, and Gutkha, with consumption patterns varying based on personal preference, cravings, and affordability. 45% of pregnant women and 55% of lactating women reported consuming SLT immediately after waking up. Economic constraints influenced product preferences and consumption frequency. Key factors influencing SLT use included peer and family influence, stress relief, pregnancy-induced craving, curiosity, individual attitude and beliefs, to remaining engaged in work. Also, the study finding shows long-term effects of SLT use among pregnant and lactating women. Notably, 52.5% (n = 21) of participants started SLT use during their adolescence and 57.5% (n = 23) had no formal education. For the enrolled pregnant women and lactating mothers, the mean age of SLT initiation was 14.95 years and 12.58 years, respectively, indicating a significantly longer history of tobacco consumption. The present study provides a detailed qualitative understanding of the use of smokeless tobacco among pregnant and lactating mothers living in low-income settings like slums. The findings of this study have strong explanations to support healthcare professionals and policymakers in undertaking interventions and promoting anti-tobacco campaigns and awareness programmes addressing the health hazards for maternal and neonatal health.